Effect of cold rolling on mechanical and corrosion properties of stabilized Al–Mg–Mn–Er–Zr alloy - D. Xue (Elsevier, 2021)
Al–Mg–Mn–Er–Zr alloy, produced through a combination of cold rolling and heat treatment process conditions, has been studied on its microstructure evolution, strengthening mechanism, and corrosion properties. The results demonstrated that, the dispersion of coherent Al3 (Er, Zr) nanoscale particles effectively pinned dislocations and increased the strength. The dislocation strengthening was considered as the primary strengthening method for Al–Mg–Mn–Er–Zr alloy. The β phase was preferentially precipitated at the grain boundary and the tip of the Al6Mn phase during annealing. The corrosion resistance of stabilized alloys was degraded after cold rolling, which can be attributed to the increase in the proportion of sub-grain stripe and high-angle grain boundaries. The alloy prepared by the process (50% deformation + 270 °C/4 h annealing + 10% deformation) exhibited a UTS of 434 MPa and a YS of 323 MPa; the degree of sensitization was quantified by the ASTM G67 test and the susceptibility to intergranular corrosion was in unsusceptible categories; this alloy thus achieves excellent mechanical properties and presents sufficient corrosion resistance.